2020
DOI: 10.3390/w13010060
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Fluctuations in the Spatial Hydraulic Jump in Stilling Basins with Different Expansion Ratio

Abstract: Pressure fluctuations are a key issue in hydraulic engineering. However, despite the large number of studies on the topic, their role in spatial hydraulic jumps is not yet fully understood. The results herein shed light on the formation of eddies and the derived pressure fluctuations in stilling basins with different expansion ratios. Laboratory tests are conducted in a horizontal rectangular flume with 0.5 m width and 10 m length. The range of approaching Froude numbers spans from 6.4 to 12.5 and the channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
6
6
1
Order By: Relevance
“…However, it can be observed that minimum values attained for C p at y/P = 2.87 (C p ~0.1) were a bit larger than those reported in the literature for hydraulic jumps [29,32,33], suggesting that, in spite of the quite uniform flow velocity field registered (Figure 7), bed pressure oscillations are not completely contained within the basin, mainly as a consequence of the reported water surface fluctuations in the area downstream from the device [34].…”
Section: Resultscontrasting
confidence: 59%
“…However, it can be observed that minimum values attained for C p at y/P = 2.87 (C p ~0.1) were a bit larger than those reported in the literature for hydraulic jumps [29,32,33], suggesting that, in spite of the quite uniform flow velocity field registered (Figure 7), bed pressure oscillations are not completely contained within the basin, mainly as a consequence of the reported water surface fluctuations in the area downstream from the device [34].…”
Section: Resultscontrasting
confidence: 59%
“…The characteristics of the fluctuating pressure of the standard stilling basin have been studied by several researchers. Toso and Bowers [5], Hassanpour et al [6] and Fiorotto and Rinaldo [7] studied the statistical structure of turbulent fluctuating pressure at the bottom of hydraulic jumps. Yan et al [8] deals with statistical analysis of pressure fluctuations at the bottom of spatial hydraulic jumps with abrupt lateral expansions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They indicated that the hydraulic jump features are strongly influenced by sill geometry. In addition, hydraulic jumps in the sudden expanding channel have been studied by many scientists (e.g., Omid et al 2010;Scorzini et al 2016;Torkamanzad et al 2019;Hassanpour et al 2021).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%